2018
DOI: 10.11648/j.ja.20180601.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spinal Anaesthesia on Penile Tumescence

Abstract: It is a common observation that following spinal anaesthesia, the penis usually elongates. The aim of this study was to determine the degree of change in penile length following spinal anaesthesia. Consecutive urosurgical patients undergoing spinal anaesthesia were recruited for this study. Those who received general anaesthesia or incomplete spinal blocked were also excluded. The flaccid length of the penis was measured before and after the administration of spinal anaesthesia. Penile length 15 minutes post-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The combined spinal technique (that is epidural and subarachnoid space block anesthesia) was chosen to confer the advantages of adequate surgical anesthesia/analgesia and safety for the obese in resource limited setting. The tumescence caused by the spinal anaesthesia [15] helped in ensuring that an appropriate size of skin graft was used to cover the penis compare with that which would have been used if the penis were in its flaccid state which would obviously restrict the penis during erection. The pathophysiology of concealed penis is still not clear but many theories regarding the cause have been proposed by many investigators, but currently it is proposed to be due to a failure of separation of the planes of migration in the developing male external genitalia, and this causes a persistence of adhesions between the planes [16].…”
Section: Discussionmentioning
confidence: 99%
“…The combined spinal technique (that is epidural and subarachnoid space block anesthesia) was chosen to confer the advantages of adequate surgical anesthesia/analgesia and safety for the obese in resource limited setting. The tumescence caused by the spinal anaesthesia [15] helped in ensuring that an appropriate size of skin graft was used to cover the penis compare with that which would have been used if the penis were in its flaccid state which would obviously restrict the penis during erection. The pathophysiology of concealed penis is still not clear but many theories regarding the cause have been proposed by many investigators, but currently it is proposed to be due to a failure of separation of the planes of migration in the developing male external genitalia, and this causes a persistence of adhesions between the planes [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted by Fyneface-ogan et al reported that there was a significant change in penile length following SA. One possible explanation is that SA impairs the sympathetic and parasympathetic innervation of the penis, leading to penile enlargement or even penile erection (14).…”
Section: Discussionmentioning
confidence: 99%
“…Priapism is a relatively rare phenomenon that may occur as a result of an imbalance between the sympathetic and parasympathetic nervous systems. This phenomenon can bring significant troubles, such as excessive bleeding, for surgeons and other medical teams during surgeries (14,15).…”
Section: Introductionmentioning
confidence: 99%